"We must find a solution now": The Ethiopian community-police relationships in Israel. (January 2023) - Yakhnich, Liat
Abstract: Members of the Ethiopian community in Israel are over-represented in the police statistics, and their relations with the police are characterized by low levels of satisfaction. This phenomenological study aimed to explore the relationships between the Israeli-Ethiopian community and the police, through the eyes of young Ethiopian adults and police officers. The data was collected through in-depth interviews with 25 participants: 13 Ethiopian young adults and 12 police officers. The data analysis yielded five themes: personal experiences with Ethiopian community-police encounters, Ethiopian youngsters' and police officers' mutual perceptions, police discrimination of Ethiopian youth, Ethiopian community-police relations, and allocating responsibility for changing the situation. The findings are interpreted in terms of Social Identity Theory and Contact Hypothesis and illustrate how the interplay between conflicting groups' identities and contact in a specific socio-political context shapes their members' mutual perceptions and affects future encounters. Implications for promoting positive intergroup relations are discussed.